Mrs. Dred Scott a life on slavery's frontier - VanderVelde, Lea. (Oxford ; New York : Oxford University Press, 2009)
In telling the life of Harriet, Dred's wife and co-litigant in the case, this book provides a compensatory history to the generations of work that missed key sources only recently brought to light. Moreover, it gives insight into the reasons and ways that slaves used the courts to establish their freedom. --from publisher description.
Wife of a celebrity -- 1835 : arriving on the frontier -- Settling in -- Entertaining guests at the Indian Agency -- Late summer harvest -- Wintering over at St. Peter's Agency -- Winters deep -- 1836 : spring and the change of the guard -- Celestial explorers -- Call of the wood as a prelude to treaty -- 1837 : treaty made before her eyes -- Marriage : together alone -- Traveling the length of the river -- New baby in a new land -- Deteriorating community -- Battles and baptisms -- Taliaferro's last stand -- Leaving Minnesota and its new tribunals -- While the doctor was away : St. Louis, 1840-43 -- House of Chouteau -- Black social life of St. Louis -- Doctor returns -- 1843 Interlude : Jefferson barracks between wars of national expansion -- Dred with the army of observation and Harriet with the children in St. Louis -- Courthouse and the jail -- Other matters at the courthouse -- Filing suit again -- 1849 : trial by pestilence, trial by fire -- Declared free -- Missouri changes its course -- Before the high court -- Aftermath and epilogue.
Includes bibliographical references (p. [443]-466) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Scott, Harriet, -- d. ca. 1870.; Scott, Dred, -- 1809-1858 -- Family; Scott, Dred, -- 1809-1858 -- Trials, litigation, etc; Women slaves -- United States -- Biography; Slaves -- United States -- Biography; Electronic books